Long‐term safety and efficacy of bimatoprost solution 0·03% application to the eyelid margin for the treatment of idiopathic and chemotherapy‐induced eyelash hypotrichosis: a randomized controlled trial. (7th March 2015) - Glaser, D.A.; Hossain, P.; Perkins, W.; Griffiths, T.; Ahluwalia, G.; Weng, E.; Beddingfield, F.C.
Summary Background Bimatoprost ophthalmic solution 0·03% is approved in several countries for the treatment of eyelash hypotrichosis. Previous trials were limited to 4 months of treatment and primarily idiopathic hypotrichosis. Objectives To evaluate the long‐term safety and efficacy of bimatoprost in patients with idiopathic or chemotherapy‐induced hypotrichosis. Methods This multicentre, double‐masked, randomized, parallel‐group study included two 6‐month treatment periods [treatment period 1 (TP1) and treatment period 2 (TP2)]. Patients with idiopathic hypotrichosis were randomized to three treatment groups: (i) bimatoprost (TP1 and TP2); (ii) bimatoprost (TP1) and vehicle (TP2); and (iii) vehicle (TP1) and bimatoprost (TP2). Patients with chemotherapy‐induced hypotrichosis were randomized to two treatment groups: (i) bimatoprost or vehicle (TP1) and (ii) bimatoprost (TP2). Primary end point was a composite of at least a one‐grade improvement in investigator‐assessed Global Eyelash Assessment and at least a three‐point improvement in patient‐reported Eyelash Satisfaction Questionnaire Domain 2 at month 4. Secondary measures included digitally assessed eyelash characteristics. Results The primary efficacy end point was met in both populations (idiopathic responder rate was 40·2% for bimatoprost vs. 6·8% for vehicle; postchemotherapy responder rate was 37·5% for bimatoprost vs. 18·2% for vehicle). Efficacy by month 6 was maintained (idiopathic) or enhanced (postchemotherapy) at 12 months. Treatment effects were maintained for approximately 2 months but markedly diminished 4–6 months following treatment cessation in patients with idiopathic hypotrichosis. No drug‐related serious adverse events were reported. Conclusions Daily treatment with bimatoprost ophthalmic solution 0·03% for 1 year was effective and well tolerated in patients with idiopathic and chemotherapy‐induced hypotrichosis.